A novel algorithm for implementing a specified wall heat flux in DSMC: Application to micro/nano flows and hypersonic flows. (20th March 2016) - Akhlaghi, Hassan; Roohi, Ehsan
Highlights: Developing a new algorithm for implementing wall heat flux B.C in the DSMC method. The model is robust enough to simulate specified wall heat flux for any geometry. Model benefits from an acceptable convergence speed in DSMC simulations. Presentation of an improved variant of the model called MIT–IT. Abstract: This paper introduces a modified version of the iterative (IT) technique called the modified iterative (MIT) technique which implements a desired wall heat flux distribution over the wall for rarefied gas simulations using the direct simulation Monte Carlo (DSMC) method. The accuracy of the MIT technique and suitable ranges of employed parameters are examined in various test cases, i.e., shear driven Couette and cavity flows, hypersonic/supersonic flows over flat plate/cylinder, and pressure-/inertia-driven flows through micro/nanochannel. In each simulated test case, rarefied gas is considered in the presence of the wall with the specified heat flux distribution. We show that the controlling factor is a critical parameter that adjusts the speed of wall temperature update. This parameter should be selected appropriately for faster solution convergence. Additional considerations in the MIT technique are also presented and investigated. The possibility of employing an efficient hybrid approach based on MIT and inverse temperature sampling (ITS) techniques for implementing the specified wall heat flux is also examined.